Genesis Analysis of Volcanic Landforms and Spatial Potential of Babadan Village as a Contextual Geography Learning Resource - Siraj Abdulkerim Yaseen; Baihaki; Risky Andias Oktavian (CV Bumi Spasial, 2026)
Volcanic landscapes represent immense potential as